FeI2-Promoted Dehydrative Coupling and Iodocyclization Reaction of 4-Hydroxycoumarins and Propargyl Alcohols for the Synthesis of Chromone Derivatives - Yoshioka, Eito; Matsuyama, Shota; Tanaka, Ryouta; Tokunaga, Iori; Yamaoka, Yousuke; Yamada, Ayaka; Miyabe, Hideto (Synthesis, 2025)
The reaction of 4-hydroxycoumarins with propargyl alcohols was studied by using FeI2. Chromone derivatives were obtained by a FeI2-promoted sequential transformation involving dehydrative coupling followed by iodocyclization. The FeI2-mediated iodocyclization of the coupling intermediates proceeded in a regioselective 6-endo-dig manner to give the chromone derivatives without the formation of coumarin derivatives.
Keywords: iron(II) iodide; dehydrative coupling; iodocyclization; 4-hydroxycoumarins; propargyl alcohols